Economies of scale and density in the Italian water industry: A stochastic frontier approach. (June 2018) - Guerrini, Andrea; Romano, Giulia; Leardini, Chiara
Abstract: The spending review carried out by many governments of the member countries of the European Union, which did away with a large part of public subsidies, recognizes that exercising control over operating and capital expenditure is one of the most important means to secure financial resources for public services. This study measures the inefficiency of 43 Italian water utilities, the main aim being to identify specific performance drivers among scale of operations, customer density, quality of water mains and wastewater treatment plants, and ownership structure. The novelty of this research lies in the procedures adopted for efficiency measurement. Besides a traditional approach to stochastic frontier analysis, the study applies true fixed effects in which time-invariant heterogeneity is introduced and kept separate from the inefficiency term. Further, we use the pairwise difference estimator for heteroskedastic normal–exponential specifications, wherein inefficiency follows a first-order autoregressive process, and we model inefficiency variance as a function of exogenous covariates. The results show that economies of scale do affect the Italian water sector, first benefiting utilities serving less than 50, 000 customers, followed by those serving 50, 000 to 150, 000 customers. Similarly, population density improves efficiency, and firms operating in densely populated areas such as cities achieve the lowest cost of delivery per cubic meter of water. This evidence not only supports the choice of the national water regulatory authority to promote aggregations of firms using the tariff method, but also suggests the importance of considering density as a relevant variable to adjust the efficiency measures. Highlights: Reducing water losses entails considerable cost and can negatively affect the firm's efficiency. The investments realized to improve the wastewater treatment plants lead to a higher inefficiency score. Regulators must promote the aggregation of water utilities in order to achieve high returns to scale. Firms wholly owned by municipalities show the highest inefficiency.